Client Narratives About Experiences With a Multicouple Treatment Program for Intimate Partner Violence. - Todahl, Jeff; Linville, Deanna; Tuttle Shamblin, Abby F.; Ball, David (Journal of Marital & Family Therapy, 2012)
A handful of clinical trials have concluded that conjoint couples treatment for intimate partner violence is safe and at least as effective as conventional batterer intervention programs, yet very few researchers have explored couples' perspectives on conjoint treatment. Using qualitative narrative analysis methodology, the researchers conducted 48 client participant interviews and five staff interviews to better understand couples' experiences of a conjoint treatment program for intimate partner violence. Themes that recurred throughout participants' narratives included (a) perceptions of safety, (b) benefits received, (c) attitudinal change, (d) behavioral change, and (e) important learning. Research directions and training implications are discussed.